(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2017)
The liberty of conscience in the context of post neo-Protestantism post takes a number of socio-political and theological dimensions induced by the technical component of the medialisation. More precisely, the changes that mark the religious practices due to their various and frequent meetings with the new technologies of mediatisation highlight the fact that these technologies are not neutral for the religious thought. To capture this phenomenon, this text provides a theoretical framework illustrated through the digital prayer understood as social assistance.